(untitled) (Journal of Universal Science Research, 2025)
Chronic kidney disease (CKD) requires long-term management, with treatment success largely depending on patient adherence and self-monitoring. Many patients, however, struggle with consistent medication use and tracking of vital health indicators. Digital tools offer new opportunities to support patients in daily disease management. “Kidney Care Community” is an interactive platform designed to enhance compliance and self-care in CKD. This study evaluates its effectiveness in improving treatment adherence and monitoring behaviors in patients with stage I–III CKD.